Economic Analysis of Elements of Civil Liability for Driving Accidents - Habibolaah Rahimi; Mohammad Ghasem Hajiyan (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2014)
One of the most important and practical topics in civil liability is driving accidents. This article considers elements of civil liability for driving accidents, and examines some rules regarding this issue. Economic analysis is one of the main methods which help legislators and policy makers to seek for effective rules and regulation.  Although numerous researches have been carried out in relation to this area, their analysis is not based on local law. The goal of this article is, rather, to elaborate major elements of civil liability for driving accidents by conducting an economic analysis based on local law.